Facilitators and Barriers of Children's Participation in Nutrition, Physical Activity, and Obesity Interventions: A Systematic Review. (7th June 2021) - Clayton, Priscilla; Connelly, Jeneene; Ellington, Malik; Rojas, Vicky; Lorenzo, Yaisli; Trak-Fellermeier, María Angélica; Palacios, Cristina
Abstract: Objectives: To conduct a systematic review of facilitators and barriers for children's participation in nutrition, physical activity, and obesity interventions from the perspective of parents, children, and researchers. Methods: Studies were identified from 5 databases and restricted to children 2–18 years and to English. Studies without results on facilitator and barriers of recruitment were excluded. Results: 423 records were identified; 97 duplicates and 269 unrelated records were initially excluded; 60 records were reviewed for full-text and subsequently 26 were excluded, for a total of 34 included studies. The top four barriers reported by children and parents were time constraints, nature of the intervention, limited understanding of clinical trial information or complexity of consent/trial info, and cost, while for researchers reported barriers were lack of transportation/lack of or childcare and time constraints. The top four common facilitators reported by children and parents were benefit others (altruism) and themselves, compensation/incentives, nature of the intervention, and quality of life, while for researchers these were physician recommendations/referrals, benefits to others and themselves, simple and clear materials describing the study and the inclusion criteria, and compensation/incentives. Conclusions: These barriers and facilitators should be addressed in future studies to assist in the successful recruitment of children into nutrition, physical activity, and obesity interventions. Funding Sources: Funding was supported by the National Institute of Health (Eunice Kennedy Shriver National Institute of Child Health and Human Development, NICHD), grant number 1R01HD098589-01.